A new SST topology comprising boost three-level AC/DC converters for applications in electric power distribution systems - Garcia Rodriguez, Luciano Andres (2017)
The growing interest in integrating distributed generation into the existing power distribution grid, the increase in the penetration levels of renewables, as well as the need to achieve a more efficient, reliable, and sustainable grid is leading to the development of new grid-interfaced power converters such as the solid-state transformer (SST). As current and voltage ratings of commercially available power semiconductor devices are normally below power ratings required in distribution systems (e.g., 13.8 kVrms), multiple modules must be connected in cascade configuration at the high-voltage (HV) side to reach higher voltage ratings as well as in parallel at the low-voltage (LV) side to achieve high current levels. A new SST topology consisting of modular boost-based three-level ac-dc converters, medium-frequency transformers with two secondary windings, and four-leg ac-dc converters is presented in this paper. When compared to similar approaches, the proposed topology comprises fewer power conversion stages, lower voltage across the semiconductor devices on the HV side, and lower current flowing through each device on the LV side. These characteristics reduce the number of series-connected modules in the HV side and parallel-connected devices in the LV side. The feasibility of the proposed topology is experimentally validated on a 500 W, 120 Vac/48 Vdc scaled-down prototype.